MARGINALIA AS A SOURCE OF BOOK HISTORY: HISTORIOGRAPHICAL ASPECT - PETREIKIS, TOMAS (Knygotyra, 2011)
Three definitions of marginalia are distinguished: codicological, polygraphic, and “postmanufaturing”. Codicologically and polygraphically marginalia are defined as additional information records which appear during the book production process. Marginalia are texts and signs (and miniatures) of a functional nature, which are usually placed behind the main text of the book. The “postmanufacturing” attitude focuses on the marginalia which have an indefinite content and which appear in the process of book functioning in society. The development of marginalia scientific studies started at the beginning of the 19th century in Great Britain, meanwhile in Lithuania it started in the sixth decade of the 20th century. In the source studies, most has been achieved in the field of initial fixing. Information about marginalia was first recorded in card catalogues, later in old prints and electronic catalogues. Half of them are published as duplicates and facsimiles. Historically, three main marginalia research trends have formed: philological, historical and book science (perceiving book history as its part). Currently, the largest work in investigating marginalia is done by researchers from Great Britain, the USA and Russia. Marginalia are invoked in the investigation of polygraphy, codicology, reading history, book culture and book art. In Lithuania, more researches in history of reading, book culture, book art, records and sign history are conducted. Historiography development possibilities are intended for the research of library, bookbindery, book trade history and biographistic studies.